A population-based registry cohort study on the correlation between bladder-intact event-free survival and overall survival in cystectomy-ineligible/refusal muscle-invasive bladder cancer patients in Sweden - Oscar Laurin; Simona Baculea; Sarah Côté; Samuel Spigelman; Robert Szulkin; Kelvin HM Kwok; Frida Schain; Christina V. Jones; Markus Aly (Scandinavian Journal of Urology)
N/A